1982
DOI: 10.1126/science.7112122
|View full text |Cite
|
Sign up to set email alerts
|

Type II Collagen Autoimmunity in Otosclerosis and Meniere's Disease

Abstract: Antibodies to collagen types I, II, and IV were measured in patients with otosclerosis and patients with Meniere's disease. Levels of antibodies to type II collagen were significantly higher in these patients than in control subjects, while no differences were found among levels of antibodies to collagen type I or type IV. These observations suggest a possible role for type II collagen autoimmunity in the etiology of otosclerosis and Meniere's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
4
3

Year Published

1983
1983
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(69 citation statements)
references
References 9 publications
0
62
4
3
Order By: Relevance
“…On immunizing rats with collagen type II lesions resembling otosclerotic foci within the otic capsule were present in animals which were observed for more than 6 months after immunization [34]. Antibodies against collagen II were described by Yoo et al [35] in the serum of patients suffering from otosclerosis and Ménière's disease. Bujia et al [36] found serum antibodies against collagen IX significantly increased in comparison with controls, while the antibodies against collagen II were not significantly raised.…”
Section: Collagen (Auto)immunitymentioning
confidence: 95%
“…On immunizing rats with collagen type II lesions resembling otosclerotic foci within the otic capsule were present in animals which were observed for more than 6 months after immunization [34]. Antibodies against collagen II were described by Yoo et al [35] in the serum of patients suffering from otosclerosis and Ménière's disease. Bujia et al [36] found serum antibodies against collagen IX significantly increased in comparison with controls, while the antibodies against collagen II were not significantly raised.…”
Section: Collagen (Auto)immunitymentioning
confidence: 95%
“…In the SV joint, on the contrary, the cartilage matrices with the lack of the CS-56 immunolabeling were vividly labeled with the type II collagen immunostaining. Previously, a hypothesis suggesting has been proposed that otosclerosis results from autoimmunoreactivity to type II collagen present in the fetal cartilaginous remnants of the human body labyrinth, based on the increased concentrations of circulating antibody against type II collagen in the patients and on the induction of otosclerosis-like lesions by immunization of rodents with cartilage collagen [31,32]. Independent researchers, however, have been unable to confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, otosclerosis is progressive disorder of temporal bone of unknown cause and pathogenesis [8]. Genetic factors are clearly involved, but measles virus infection and autoimmunity to collagen type II also might play contributing roles [5,14,17,18,25,32]. The most common location of an otosclerotic focus is the otic capsule anterior to the stapes footplate [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relapsing polychondritis [1,2] is a rare systemic autoimmune disorder of unknown origin characterized by episodic inflammation of cartilaginous tissues throughout the body where collagen type II (CII) is the major protein [3,4,5,6]. Elastic cartilage of the ears and nose, hyaline cartilage of peripheral joints, vertebral fibrocartilage, tracheobronchial cartilage, as well as proteoglycan-rich structures of the inner ear, eye, heart, or blood vessels may all be affected.…”
Section: Introductionmentioning
confidence: 99%